Respon Fisiologi dan Perilaku makan Kerbau Lumpur (Bubalus bubalis) dengan Jarak Penggembalaan yang Berbeda pada Sistem Silvopastura - Sartono, D. Z.; Priyanto, R.; Putra, B. W. (Jurnal Sain Peternakan Indonesia, 2025)
Mud buffalo (Bubalus bubalis) is one of Indonesia's livestock commodities with a high potential to be developed. However, its utilization has not been optimized to the fullest. This study aims to evaluate the effectiveness of the silvopasture system in improving mud buffalo welfare based on physiological responses and feeding behavior. This study was conducted in Peguyangan Village, Bantarbolang Subdistrict, Central Java Province. Ninety-one buffaloes were observed using a purposive sampling technique grouped by sex and age. Variables observed included grazing distance, environmental temperature and humidity, physiological responses, Heat Tolerance Coefficient (HTC) values, and feeding behavior. T-test analyzed data. The results showed the highest body temperature (38.08 ˚C) in adult male buffaloes with a grazing distance of 5 km. Buffaloes grazed within an 8 km radius had higher respiration rate (42.48±2.67 bpm) and travel speed (1.14 km/h), with shorter feeding duration (03:18 minute) compared to a 5 km distance (03:57 minute). HTC analysis showed low heat tolerance in both regions. Feeding behavior was observed more frequently in female buffaloes. Silvopasture systems integrated with teak forests can provide adequate nutrition, with grazing distance influencing physiological adaptations.